Bacteriological Profile and Antibiotics Susceptibility Patterns of Complicated Skin and Skin Structure Infections in Tertiary Care Hospital - Syed Bilal Ahmed, Sajida Jabeen (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Complicated skin and skin structure infections are most prevalent and are mostly caused by gram positive and gram negative bacteria but unfortunately these bacteria are often resistance to the commonly prescribed antibiotics. Objective: The present study main objective was to find out the Bacteriological profile and antibiotics susceptibility patterns of complicated skin and skin structure infections in tertiary care hospital. Materials; and method: The current cross-sectional study was carried out PGMIQ/ BMC Hospital Quetta from June 2022 to November 2022 after taking permission from the ethical board of the institute. Individuals of both gender and different age groups with skin infection were included. In accordance with hospital sample collection policy, all pertinent samples were gathered from contaminated places. Every pus/wound swab sample was handled in accordance with accepted microbiological laboratory practices. Using biochemical assays, isolates were frequently identified down to the species level. According to the 2012 CLSI, susceptibility testing was conducted and various antibiotics were used. All the data was analyzed through SPSS version 23 and presented in frequency and percentage. Results: A total of 440 individuals participated in the current study of which females were 184(41.8%) and male were 256(58.1%). The most prevalent kind of infection was abscesses, which were followed by skin ulcers. Among gram positive bacteria the most prevalent isolated Bactria was S.aureus 26.5% followed by MRSA 9.6% while among gram negative bacteria E.coli was the most common bacteria 17.5% followed by Pseudomonas aeruginosa 14.1% . It was found that all gram-positive isolates were sensitive to vancomycin. It was noted that gram-negative isolates were resistant to the majority of the tested antibiotics. All isolates were found to be sensitive to tigecyline, making it the most effective medication. The majority of the isolates were found to be susceptible to tazobactam+ pipiracillin, gentamicin, amikacin, meropenem, ticarcillin, chloramphenicol. Conclusion: The current study concluded that the most prevalent organisms that is likely to be found in skin and soft tissue infections, were S. aureus followed by E. coli and Pseudomonas species. To combat these pathogens, empirical treatment could include aminoglycosides, ciprofloxacin, and vancomycin. Keywords: Bacteriological profile; Antibiotics; Susceptibility; Complicated skin and skin structure infections